MAKNA “GOOD GOVERNANCE” DARI PERSPEKTIF ILMU POLITIK - I Gusti Ngurah Wairocana (Perspektif, 2006)
From political science perspective, the nature of good governance is proliferation of liberalism by moneter international institutions. Good governance is one of the requirement for a recivier state of loans from the moneter international institutions. Good governance was synergy of stakeholders (government, privat sector, and society) in the implementation of government. Good governance aims to empowering the participation of society in the process of policy formulation, and finally to create a democratic government.